Threshold Size Effects in the Patterned Crystallization of Hybrid Halide Perovskites for Random Lasing. Issue 3 (4th February 2021) - Hu, Jingyun; Wang, Meng; Tang, Fawei; Liu, Miao; Mu, Yunyun; Fu, Yulan; Guo, Jinxin; Song, Xiaoyan; Zhang, Xinping
Abstract : A threshold effect in the periodical patterning of the hybrid halide perovskites and a directional output coupling effect in the incoherent random lasing from the patterned materials are reported. Using 1D gratings, the random crystallization process is confined into the grating grooves, producing continuous microstrips of CH3 NH3 PbBr3 along the groove channels. However, the confinement is strongly dependent on the width of the grating grooves, which can be optimized by tuning the patterning periods. It is thus discovered that the most orderly arranged crystal strips are achieved for a grating period of 10 μm, corresponding to a channel width of about 5 μm, which is the lower limit for the formation of continuous crystal strips. Complicated interfaces inside such randomly organized multicrystals supplied scattering centers for optical gain mechanisms. Thus, incoherent random lasing actions are observed for all of these patterned structures, however, the best lasing performance is achieved for a grating period of 10 μm, which agrees with the highest quality of the crystal strips. The patterned substrate with a 1D grating supplies mechanisms for directional crystallization of hybrid halide perovskites and directional output coupling of random laser emission, enhancing significantly the practical application possibilities of such random lasers. Abstract : Directional output coupling of random lasing is achieved in the periodically patterned CH3 NH3 PbBr3 (MAPbBr3 ). A threshold effect is discovered with the channel width for achieving complete confinement of MAPbBr3 into the grating grooves and producing continuously distributed microstrips of crystallized MAPbBr3 . At the threshold channel of about 5 μm, the best random lasing performance is observed.